PELATIHAN DAN PENDAMPINGAN KEWIRAUSAHAAN KREATIF BAGI SISWA SMK UNTUK MENDUKUNG P5 KURIKULUM MERDEKA - Mustafida, Nurul; Kartika, Titis Puspitaningrum Dewi; Kholid, Ikhwan; Tianto, Reza; Mursita, Lufi Yuwana; Permata, Aulia Safnira Surya (Universitas Mataram, 2024)
This community service activity is motivated by the need for knowledge and skills and supports achieving the Independent Curriculum P5 Project for students. The P5 program is also designed to strengthen efforts to achieve competency and character according to the Pancasila Student Profile, which is prepared based on Graduate Competency Standards (SKL). The urgency of implementing the P5 Independent Curriculum still needs to be felt heavily. It is causing problems in the school environment, especially at Wahid Hasyim Glagah Lamongan Vocational School, regarding the readiness of teacher and educator resources. Therefore, the Hayam Wuruk Perbanas University implementation team provided this community outreach activity in the form of creative entrepreneurship training and assistance. The Merdeka P5 curriculum utilizes interactive learning methods and allows students to participate actively in the learning process. Creative entrepreneurship mentoring and training aims to explore students' potential, knowledge, and entrepreneurship skills that impact the surrounding community. This activity is designed in four stages, namely, the material preparation stage, entrepreneurship training, assistance with business activities, and processing and presenting the activity results. The implementation team prepares material in the preparation stage, which will be delivered at the training stage. At the training stage, material related to creative entrepreneurship will be presented, and two teams with the best business ideas will be selected. The final stage is the presentation of the results of activities in the form of reports related to the implementation of training and mentoring activities. Based on results, 67% of participants experienced an increase in test scores between the pre-test and post-test, 14% of the total participants had the same score, and the remaining 18% experienced a decrease in test scores. This shows that students' knowledge of entrepreneurship concepts, entrepreneurial activities, and basic Business Model Canvas (BMC) concepts increased after they received creative entrepreneurship training materials. Based on these results, the implementation of the training showed excellent and effective results because more than 50% of participants experienced an increase in knowledge. The training also produces business ideas from students, followed by realizing business ideas into business products. The students whose business ideas were selected were given entrepreneurial assistance related to the product preparation process, packaging design, marketing process, and simple financial record keeping.